A Model-Based Cost-Effectiveness Analysis of an Exercise Program for Lung Cancer Survivors After Curative-Intent Treatment. (March 2020) - Ha, Duc; Kerr, Jacqueline; Ries, Andrew L.; Fuster, Mark M.; Lippman, Scott M.; Murphy, James D.
Abstract : Objective: The cost-effectiveness of exercise interventions in lung cancer survivors is unknown. We performed a model-based cost-effectiveness analysis of an exercise intervention in lung cancer survivors. Design: We used Markov modeling to simulate the impact of the Lifestyle Interventions and Independence for Elders exercise intervention compared with usual care for stage I–IIIA lung cancer survivors after curative-intent treatment. We calculated and considered incremental cost-effectiveness ratios of less than US $100, 000/quality-adjusted life-year as cost-effective and assessed model uncertainty using sensitivity analyses. Results: The base-case model showed that the Lifestyle Interventions and Independence for Elders exercise program would increase overall cost by US $4740 and effectiveness by 0.06 quality-adjusted life-years compared with usual care and have an incremental cost-effectiveness ratio of US $79, 504/quality-adjusted life-year. The model was most sensitive to the cost of the exercise program, probability of increasing exercise, and utility benefit related to exercise. At a willingness-to-pay threshold of US $100, 000/quality-adjusted life-year, Lifestyle Interventions and Independence for Elders had a 71% probability of being cost-effective compared with 27% for usual care. When we included opportunity costs, Lifestyle Interventions and Independence for Elders had an incremental cost-effectiveness ratio of US $179, 774/quality-adjusted life-year, exceeding the cost-effectiveness threshold. Conclusions: A simulation of the Lifestyle Interventions and Independence for Elders exercise intervention in lung cancer survivors demonstrates cost-effectiveness from an organization but not societal perspective. A similar exercise program for lung cancer survivors may be cost-effective.